Uma análise sobre o conselho fiscal : o ativismo e monitoramento nas empresas de capital aberto no Brasil - Silva, Layziane Souza (2017)
Activism research have grown in the last decade, especially in Anglo-Saxon countries. Gillan and Starks (2007) define activism as an attempt of minority shareholders to bring changes in the company without a control change. In Brazil there are few studies on the subject and there are rare studies on the fiscal board. This study addresses the request for the establishment of the fiscal board in Brazilian publicly traded companies as an activist initiative. The goal is to examine the determinants of this request, with emphasis on proxies of monitoring. The sample used was composed by Brazilian companies listed on the São Paulo Stock Exchange (BM & FBovespa), with annual liquidity above 0.001, in the period of 2010, 2012, 2014 and 2016. Data were collected at the base of Comdinheiro dataset and in Ordinary General Meetings of the companies, available on the website of the Brazilian Securities and Exchange Commission (CVM) or BM&FBovespa. To achieve the objective, a monitoring index was formulated with seven questions involving topics such as ownership structure, independence and size of the board and coverage of analysts. The methodology adopted included descriptive analyzes, univariate tests and logistic regressions. As important results found, it was evidenced that the number of companies that were requested by the fiscal boar, which were not requested and have a permanent fiscal board are similar in numbers. The central hypothesis of this work, cannot be proven through the monitoring index, but through its components it was possible to observe that some characteristics of the monitoring are relevant. Being accompanied by at least three market analysts negatively influences the chances of requesting the installation of the fiscal council. For the chances of having permanent fiscal council also negatively influence the existence of a controlling shareholder and the size of the appropriate board. The observed control variables showed that a higher indebtedness and a lower Market-to-book increase the chances of requesting a fiscal council. For the adoption of permanent advice size and Market-to-book influence positively. In general, the adoption of the fiscal council, whether on a permanent or temporary basis, is related to a need for greater monitoring by the shareholders.